Small-Scale Habitat-Specific Variation and Adaptive Divergence of Photosynthetic Pigments in Different Alkali Soils in Reed Identified by Common Garden and Genetic Tests - Qiu, Tian; Jiang, LiLi; Li, ShanZhi; Yang, YunFei (Frontiers in Plant Science, 2017)
Flexibility of photosynthetic pigment traits is an important adaptive mechanism through which plants can increase mean fitness in a variable environment. Unlike morphological traits in plants, photosythesis has been shown to exhibit phenotypic plasticity, responding rapidly to environmental conditions. Meanwhile, local adaptation at small scales is considered to be rare. Thus, detecting the small-scale adaptive divergence of photosynthetic pigments presents a challenge. Leaf concentrations of photosynthetic pigments under stressful conditions may be reduced or maintained. Concentrations of some pigments and/or ratio of Chlorophyll a (Chla) to Chlorophyll b (Chlb) do not change markedly in some species, such as the common reed, Phragmites australis, a cosmopolitan grass and common invader. Little is known about photosynthetic responses of this plant to varying levels of alkali salt. Few studies have attempted to account for the relationship between pigment accumulation and leaf position in wild plant populations in grasslands. In this study, photosynthetic pigment concentrations and the total Chl(a+b) /Car ratio decreased as the growing season progressed and were shown to be significantly lower in the habitat with a higher soil pH value and less moisture when compared between habitats. The Chla/Chlb ratio did not differ significantly between habitats, although it increased significantly over time. Leaves in the middle position may be functionally important in the response to soil conditions because only pigment concentrations and the Chl(a+b) /Car ratio of those leaves varied between habitats significantly. The outlier loci, used to evaluate molecular signatures of selection, were detected by Arlequin, Bayescan and Bayenv analyses. In the simulated habitats of common garden, the local genotypes had higher values of Chla, Chlb, Chl(a+b), Car in their home habitat than did genotypes originating from the other habitat. QST–FST comparisons provided evidence of divergent selection. It appears likely that soil moisture, pH and electric conductivity drove local adaptation. Combined approaches that utilize information on phenotypes from field and common garden experiments, genome-wide markers, and environmental data will be the most informative for understanding the adaptive nature of the intraspecific divergence.